Phenytoin Versus Levetiracetam for Post-traumatic Seizure Prophylaxis - Tuğçe Mengi; Barış Yılmaz; Uğur Koca; Ali Necati Gökmen (Türk Yoğun Bakim Derneği Dergisi, 2022)

(untitled)
Objective:This study aimed to compare the efficacy of levetiracetam versus phenytoin in early post-traumatic seizure prevention and ascertain the incidence of clinical seizures in traumatic brain injury (TBI).Materials and Methods: Adult patients with moderate to severe TBI in the neuroimaging consistent with brain injury were included in the study. Patients were categorized into two groups, the phenytoin or levetiracetam groups, based on the administration of antiepileptic drugs for seizure prophylaxis.Results:In this study, 100 patients with TBI met the inclusion criteria between January 2012 and June 2017, wherein 60 received seizure prophylaxis with phenytoin, and 40 with levetiracetam. The incidence of early post-traumatic seizure was 8%, without significant differences between groups (p>0.05). The incidence of clinical seizures after TBI was 10%.Conclusion:This report showed that levetiracetam and phenytoin had similar efficacy in posttraumatic seizure prophylaxis. This retrospective study design improved the reliability of comparison between phenytoin and levetiracetam for seizures in the two groups with similar features in terms of age, sex, injury mechanism, neuroimaging findings, and Glasgow coma, Marshall, and acute physiology and chronic health evaluation-II scores.